GAMBARAN PASIEN GERIATRI MELAKUKAN SWAMEDIKASI DI KABUPATEN SLEMAN - Woro Supadmi (Pharmaciana, 2013)
The increase in life expectancy caused geriatric population is also increasing. Geriatric patient is identical to the decline in physiological function that can lead to various diseases. Self medication in geriatric require special attention from the pharmacist. The purpose of this study was to determine the description of geriatric that does self medication and assosation factors in geriatric patients doing the self medication in Sleman. This research was conducted using a survey to determine the presence of pharmacy in Sleman. Determination of pharmacies conducted with a purposive sampling technique and determination of areas of research subjects or respondents with accidental sampling. Subjects were geriatric patients with age> 60 years who did self medication in pharmacies. The data were analyzed by using chi-square statistic to determine which are the most influential association factors. The research subjects in this study was 38 respondents. The pattern of disease that occur in geriatric patients who performs a self-medication is a chronic 12 respondens, non-respondens and 16 non chronic respondens ten respondens is unknown. Factors that association geriatric patients that is doing self medication is own of health insurance. The results of the chi square test showed that the sex factor with OR 1,11 ( p >0,05), ownership asurance (OR = 1,841,p < 0,05,CI : 1,184 – 2,184) is a factor of self association with geriatric patients medications at the pharmacy of district Sleman.